Therapeutic Targeting of Fibrotic Epithelial-Mesenchymal Transition–An Outstanding Challenge - Fintha, Attila; Gasparics, Ákos; Rosivall, László; Sebe, Attila (Frontiers in Pharmacology, 2019)
Back in 1995 a landmark paper was published which shaped the fibrosis literature for many years to come. During the characterization of a fibroblast specific marker (FSP1) in the kidneys, an observation was made which gave birth to the hypothesis that “fibroblasts in some cases arise from the local conversion of epithelium”. In the following years epithelial-mesenchymal transition was in the spotlight of fibrosis research, especially in the kidney. However, the hypothesis came under scrutiny following some discouraging findings from lineage tracing experiments and clinical observations. In this review we provide a timely overview of the current position of the epithelial-mesenchymal transition hypothesis in the context of fibrosis (with a certain focus on renal fibrosis) and highlight some of the potential hurdles and pitfalls preventing therapeutic breakthroughs targeting fibrotic epithelial-mesenchymal transition.